Still Life with Timex : Poems - Murawski, Elisabeth, 1936- (Book collections on Project MUSE., 2021)
""Still Life with Timex" chronicles a mother's loss. These poems explore the unsightly aspects of grief and the survivor's guilt of outliving a child"--